How to motivate employees to engage in online knowledge sharing: Differences between posters and lurkers - Nguyen, Tuyet Mai; Malik, Ashish; Sharma, Piyush (Emerald, 2020)
Purpose-This study combines the theory of planned behave or (TPB) and the motivational framework to extend the research on online knowledge sharing (OKS) in an organization by exploring the factors that drive the knowledge sharing intentions (KSI) of posters and lurkers.